ANALYSIS NETWORK INSTALLATION ON INDIHOME AND DOUBLE CONFIGURATION ON DASHBOARD VOICE SERVICE SURVEILLANCE TREG-3 - Islamia Nuraini (Journal Publicuho, 2023)
The projects related to management system and business processes have a low risk in every job. This method can be done in overcoming installation problems on Indihome that add performance to customers consists of an aggregate effort to perform maintenance by effectively utilizing and material through the application standard procedures that the company has to develop the system. The business orientation has a correlation between production process focus and performance at the business unit level using the profit impact of marketing strategies database. The relationship between production process focus and financial performance for business units was partially supported using return on sales, and was not supported with return on assets and return on income. The companies have prioritized this Enterprise Resource Planning (ERP) plan to manage their daily business activities, such as financial management, procurement, production, projects, human resources, and others. The system can facilitate businesses with real-time and accurate information. The implication is hase degree of production process focus must be recognized as part of a manufacturing strategy that is consistent with an overall business strategy. The method has purpose problems found in the network installation on Indihome and double configuration contained of voice service Treg-3 surveillance to reduce the obstacles that occur in customers. The case study uses the Network Installation method, Activity Diagram, Use Case Diagram, Deployment Diagram, DFD level 0, DFD level 1, DFD level 2